Genomics and Geographic Diversity of Bacteriophages Associated With Endosymbionts in the Guts of Workers and Alates of Coptotermes Species (Blattodea: Rhinotermitidae) - Chen, Junyan; Gissendanner, Christopher R.; Tikhe, Chinmay V.; Li, Hou-Feng; Sun, Qian; Husseneder, Claudia (Frontiers in Ecology and Evolution, 2022)
Subterranean termites depend nutritionally on their gut microbiota, which includes protozoa as well as taxonomically and functionally diverse bacteria. Our previous metavirome study revealed a high diversity and novel families of bacteriophages in the guts of Coptotermes formosanus workers from New Orleans, Louisiana, United States. Two assembled bacteriophage genomes (Phages TG-crAlp-04 and 06, family Podoviridae) existed in all colonies and showed similarity to a prophage (ProJPt-Bp1) previously sequenced from a bacterial endosymbiont (Candidatus Azobacteroides pseudotrichonymphae, CAP) of protozoa in the gut of a termite species of the genus Prorhinotermes from Taiwan. In this study the genomes of Phage TG-crAlp-04 and 06 were subjected to detailed functional annotation. Both phage genomes contained conserved genes for DNA packaging, head and tail morphogenesis, and phage replication. Approximately 30% of the amino acid sequences derived from genes in both genomes matched to those of ProJPt-Bp1 phage or other phages from the crAss-like phage group. No integrase was identified; the lack of a lysogeny module is a characteristic of crAss-like phages. Primers were designed to sequence conserved genes of the two phages and their putative host bacterium (CAP) to detect their presence in different termite species from native and introduced distribution ranges. Related strains of the host bacterium were found across different termite genera and geographic regions. Different termite species had separate CAP strains, but intraspecific geographical variation was low. These results together with the fact that CAP is an important intracellular symbiont of obligate cellulose-digesting protozoa, suggest that CAP is a core gut bacterium and co-evolved across several subterranean termite species. Variants of both crAss-like phages were detected in different Coptotermes species from the native and introduced range, but they did not differentiate by species or geographic region. Since similar phages were detected in different termite species, we propose the existence of a core virome associated with core bacterial endosymbionts of protozoa in the guts of subterranean termites. This work provides a strong basis for further study of the quadripartite relationship of termites, protozoa, bacteria, and bacteriophages.